Nonlinear Simulation of Beam Elements Subjected to High Mass Low Velocity Impact Loading using the Smoothed Particle Hydrodynamics (SPH) Method - Mokhatar, Shahrul Niza; Yoshimi, Sonoda; Mohd Jaini, Zainorizuan (International Journal of Integrated Engineering, 2013)
In this paper, a fully Lagrangian method namely as Smoothed Particle Hydrodynamics (SPH) has been utilized in order to simulate the response of reinforced concrete beam subjected to low velocity impact loading. Models based on this method are proposed to capture an important failure mechanism on compression and tension of the beam elements under dynamic (impact) loading condition. Pressure dependant criterion known as Drucker-Prager (DP) with a new Plane-Cap (PC) yield surface were employed to concrete, and (Von-Mises) criterion was applied for steel reinforcement. The constitutive equation of PC model is employed on compression, while, orthotropic constitutive equation due to the damage effect is considered on tension. Meanwhile, Dynamic Increase Factor (DIF) was defined separately for the effect of strain rate (SR) on the concrete and steel reinforcement. Shear cracking, bending cracking and compressive behavior of the beam were evaluated by using displacement-time histories and overall failure mode. Then, the applicability and efficiency of the proposed models were validated with experimental tests through numerical simulations with different velocity (height of drop-mass).